Mechanical and Thermal Properties Analysis on Bitumen Mixture with Additives: HDPE, PP and Lignin - Junior, Adream Bais; Prawira, Yermia Andri; Chalid, Mochamad; Taning, Ahmad Z.; Nugraha, Adam Febriyanto (Program Studi Teknik Mesin Universitas Pamulang, 2024)
This study focuses on enhancing the performance and sustainability of asphalt materials in road construction by recycling High-Density Polyethylene (HDPE). Polypropylene (PP) and lignin as additives in bitumen. The Hot Melt Mixing method is employed to investigate the impact of different concentrations of HDPE, PP, and lignin on bitumen properties. Key properties such as ductility, penetration, softening point, and thermal behavior are analyzed, providing valuable insights into the potential of these additives to enhance bitumen performance. The findings demonstrate that higher concentrations of HDPE and PP result in reduced penetration depth, indicating increased hardness. The addition of lignin enhances penetration depth, contributing to the flexibility and performance of the bitumen mixture. Moreover, thermal analysis offers valuable information about the thermal behavior and stability of the bitumen-plastic-lignin blends, shedding light on their compatibility and interactions. This research contributes to the ongoing efforts in road construction and pavement engineering by exploring sustainable solutions that not only address plastic waste challenges but also improve the performance and durability of bituminous materials, making it a crucial step towards environmentally responsible and long-lasting asphalt pavements.